Legionnaires' disease prevention: more doubts than certainties (Italian Journal of Public Health, 2004)
This short paper focuses on some of the troubling issues concerning Legionnaires’ disease prevention.Examples of such are its constant under-reporting, the lack of consensus concerning environmental surveillance (when and where these tests should be performed) as well as the threshold for Legionella colonisation (CFU/L).Even environmental treatment aspects are not completely agreed upon by all researchers.